LOYALITAS PELANGGAN DITINJAU DARI KERAGAMAN PRODUK, KUALITAS PRODUK DAN KUALITAS PELAYANAN DI SAKAW COFFEE & BITES KARANGANYAR - Rahmat Gunawan; Sri Hartono; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2021)
The development of the culinary industry in Indonesia has experienced a rapid increase, in this condition the competition has become fierce to get and retain customers. This study aims to examine product diversity, product quality and service quality towards customer loyalty of Sakaw Coffee & Bites. The sample research sample is 100 consumers accidental sampling with multiple linear regression method. The results of the research on product diversity, product quality and service quality simultaneously and partially have a significant effect on customer loyalty of Sakaw Coffee & Bites. The contribution of the three independent variables can explain customer satisfaction by 47.9% and the rest is influenced by other variables. Keywords: product diversity, product quality and service quality, customer loyalty